1999
DOI: 10.1002/(sici)1097-0223(199911)19:11<1055::aid-pd681>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal diagnosis of a fetal left atrial diverticulum

Abstract: Fetal echocardiography, performed on a 22-year-old woman at 31 weeks' gestation, revealed a diverticulum of the left atrium. The size of the diverticulum was similar to the size of the fetal heart in a four-chamber view. No evidence of congestive heart failure or changes in size of the diverticulum were observed on subsequent ultrasound examinations. The echocardiographic image suggested presence of a thrombus within the diverticulum. Echocardiography of the newborn confirmed the diagnosis, and surgical correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 9 publications
0
14
1
Order By: Relevance
“…Such lesions arise most commonly from the ventricles. However, a few reports have documented cases emanating from an atrial chamber [3][4][5][6] . Adverse outcomes in these cases have been associated with the size of the aneurysm, the area of cardiac hypokinesis, and the presence of fetal hydrops due to low output failure.…”
Section: Introductioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Such lesions arise most commonly from the ventricles. However, a few reports have documented cases emanating from an atrial chamber [3][4][5][6] . Adverse outcomes in these cases have been associated with the size of the aneurysm, the area of cardiac hypokinesis, and the presence of fetal hydrops due to low output failure.…”
Section: Introductioncontrasting
confidence: 76%
“…The cases of fetal atrial aneurysms in the literature report diverticula arising from either the atrial septum 3,4 or from the remainder of the atrial wall 5,6 . However, abnormalities arising in the atrial septum may represent normal variations of closure of the foramen ovale 3 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The normal anatomy of the left atrial appendage has also been well studied [13]. During the routine clinical performance of coronary CT angiograms using a 64 slice ECG-gated CT scanner we have occasionally observed additional variations in the anatomy of the left atrium which are unusual and have been reported before as case reports or in small studies, such as atrial diverticuli [14][15][16][17][18], atrial aneurysms [19][20][21] and small accessory veins or fistulas originating from the left atrium which might look like diverticuli [12]. In this study we present an observational study of left atrial accessory appendages, and we report on the frequency and appearance of these lesser known anatomical variations of the left atrium in patients presenting for a clinical coronary CT angiogram using a 64 slice CT scanner.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of dual-source CT, small left atrial diverticula are detected as common anatomic structures with a prevalence of more than 30% [3]. There have been isolated reports of very large left atrial diverticula that extend to the apex of the heart over the ventricular surface [1,2,4,5]. To our knowledge, this is one of the largest left atrial diverticula to be reported.…”
Section: Commentmentioning
confidence: 99%